Experimental investigation of the strength of fire-damaged concrete depending on admixture contents. (16th May 2023) - Chun, Yeonju; Kwon, Jaesun; Kim, Jeongwoo; Son, Heeju; Heo, Soyoung; Cho, Suyeon; Kim, Heesun
Highlights: Admixtures such as fly ash and blast furnace slag were commonly added to concrete for substituting cement but not thoroughly studied when exposed to high temperature. Compressive strength changes of different mixture ratios after exposed to high temperature were observed by conducting loading test, Raman spectroscopy, and SEM analyses. When exposed to 200 °C, fly ash composite concrete shows the highest strength while when exposed to 500 and 800 °C, pure cement and fly ash-slag composite concrete show the highest strength, respectively. C-S-H peak in Raman spectroscopy is observed in 200 °C for all three specimens. However, when exposed to 500 °C, C-S-H peak is selectively captured and C-S-H peak is not found when exposed to 800 °C. Abstract: This study investigates whether the inclusion of fly ash and blast furnace slag in concrete mixtures affects the compressive strength of concrete exposed to high temperatures. When the specimens were exposed to 200 °C, fly ash composite concrete shows the highest strength and C-S-H peak in Raman spectroscopy is observed for all three specimens. When the specimens were exposed to 500 °C, pure cement concrete shows the highest strength and C-S-H peak is selectively captured while when the specimens were exposed to 800 °C, fly ash-slag composite concrete shows the highest strength and C-S-H peak is not found.